Employees’ commitment and organizational change: the role of subordinates - Head of Department Relationship - Sulaiman Tahajuddin; Abdul Wahid Mohd Kassim; Jainurin Justine (Universiti Malaysia Sabah, 2020)
During the past decade, a number of developing countries have introduced radical reforms especially in the aspect of public service delivery system. Malaysia as one of the developing countries has as well been experiencing numbers of public sector reforms which includes the introduction of the Goods and Services Tax (GST) in April 20152. Within this context, it is argued that the employees’ organizational commitment is an imperative and vital element in boosting the productivity and service delivery quality of the organization. This paper is about the issues pertaining to the effect of the employees - head of department relationship in the process of organizational change. The data is primarily gathered from the survey questionnaires administered to the Royal Malaysian Customs Departments (RMCD) employees from all level of positions throughout Malaysia. It is found that the nature of the relationship between the subordinates and their head of departments are significantly affecting the success of the GST implementation in Malaysia which the organizational change in this case. Future research should take into considerations other influential elements such as the employees’ motivation, and leadership style in the study to further enrich the related body of knowledge.